Day 3 Wed, March 08, 2017 2017
DOI: 10.2118/183879-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Alternative Waterflood Designs and Operations Using Streamline Simulation: Application to an Oil Field in the North German Basin

Abstract: A pattern flood management method based on a streamline simulator was developed to support waterflood designs. The methodology was applied on a structurally complex oil field in the North German basin. Studies are being conducted to understand the potential for extending the current waterflood in this oil field. The objective of this study was to investigate if a conventional simulation-based waterflood design could be enhanced using streamline simulation. An alternative to using streamline simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…While (Bouaouaja et al 2012) conventionally determined producer/injector interrelationships based on constant (i.e., fixed) predefined patterns, several authors successfully utilized streamlines technology in fieldscale studies and demonstrated a more accurate representation of the dynamic irrigation/drainage regions within the reservoir (Thiele and Batycky 2003;Spyrou et al 2017;Liu et al 2010). For example, Thiele et al (2010) used streamlines to provide great insights about the strength of connectivity between wells and paths followed by water to connected producers as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…While (Bouaouaja et al 2012) conventionally determined producer/injector interrelationships based on constant (i.e., fixed) predefined patterns, several authors successfully utilized streamlines technology in fieldscale studies and demonstrated a more accurate representation of the dynamic irrigation/drainage regions within the reservoir (Thiele and Batycky 2003;Spyrou et al 2017;Liu et al 2010). For example, Thiele et al (2010) used streamlines to provide great insights about the strength of connectivity between wells and paths followed by water to connected producers as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%